A Practical method for risk assessment in power transformer fleets (2017)
A useful tool to support the decision-making process in power transformer management is risk assessment. There are few practical methodologies to assess a Transformer Risk Index (TRI). In addition, such proposals do not consider the latest advances in techniques for transformer health valuation, and they also have other drawbacks. This paper proposes a practical method to undertake risk analysis of power transformer fleets, which deal with the stated problem. The proposal appropriately considers the best attributes of the methods reported in literature in order to compute the two components of TRI, i.e., the failure probability factor and the consequence factor. Moreover, this paper contributes to the risk analysis issue by including risk matrices and clustering techniques to support the decision-making process. The presented method was tested on a fleet of fourteen transformers. This approach serves as a practical and reliable tool for asset management in power utilities.